Cadmium Toxicity: Sources, Mechanisms and Human Health Implications: A Comprehensive Review - Purushottam, B.; Reddy, R. Adhinarayana (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Objectives: This comprehensive review thoroughly explores cadmium toxicity, covering its detection methods, sources, biological pathways, health risks, related challenges, and strategies for prevention and treatment. Methodology: literature analysis on the toxicological effects of Cadmium on human health by utilizing databases like PubMed, Web of Science, and Google Scholar, which include reputable publications and peer-reviewed journals (2019-2024). Keywords such as "Cadmium toxicity," "Cadmium exposure," "human health effects," and others were used to gather relevant studies. Results: Cadmium, a harmful metal, is a significant environmental pollutant that leads to oxidative stress, cell harm, hemolytic anemia, and disruption of neurotransmitters, causing severe health problems and organ damage, which can be fatal in severe cases. Discussion: Cadmium's adverse impacts on human health are substantial, resulting in renal dysfunction, bone demineralization, respiratory problems, and carcinogenesis. Children and pregnant women are among the most vulnerable demographics. Strategies include stringent legislation, public education, and effective treatment regimens. Conclusion: Cadmium poisoning offers a health risk, necessitating interdisciplinary collaboration among scientists, healthcare professionals, politicians, and public health advocates to detect, prevent, and treat contamination efficiently.